Celiac disease and gluten-free diet: past, present, and future - Makovicky, Peter (Gastroenterol Hepatol Bed Bench, 2020)
A gluten-free diet is a special type of diet intended for people with celiac disease. The objective of this article is to report the past, present production, supply of gluten-free products as well as their future position in our market. In the past, there were only limited gluten-free products available and the awareness of the diet was limited to paediatric community. There were only few raw gluten-free materials and almost all the production was created in households. Later with the introduction of targeted screening into the practice, celiac diagnosis has improved, with an increase in newly diagnosed patients who have remained life-long dependents on a gluten-free diet. This was associated with an increased production of gluten-free products, referred to as weight loss diet, with their positive effects on health. Subsequently, the gluten-free diet has also been voluntarily adopted by both people with other diseases and healthy individuals. In the future, the gluten-free diet consumption is expected to increase, due to its increased popularity in populations. In this regard, gluten-free diets have been misinterpreted as a "miracle drug" that is effective on a variety of problems. The medical community will be confronting the future problems of people who are dependent on a gluten-free diet as well as the complications arising from the consumers of a gluten-free diet for no medical reasons. Compliance to the principles of a gluten-free diet should be maintained and should not be recommended to healthy individuals or those without relevant reasons.